DIFFICULTIES AND FACILITATING ASPECTS IN THE UNDERTAKING OF HOME VISITS IN A PSYCHO-SOCIAL CARE CENTER - Marivana Fernandes; Maria de Lourdes Custódio Duarte; Joice Moreira Schmalfuss (Universidade Federal do Paraná, 2014)
This study aims to analyze the difficulties and facilitating aspects faced by professionals of a Psychosocial Care Center in the south of Brazil in the undertaking of home visits. It is a qualitative approach and was undertaken based on semi-structured interviews held in November 2012 with nine professionals who undertook home visits. The analysis of the data allowed the emergence of two categories: difficulties faced by the professionals in undertaking home visits; and aspects which facilitate the undertaking of home visits. Conclusions are made regarding the importance of health managers providing sufficient material and human resources for meeting the demands of the home visits, as well as making it possible to be trained to carry out this care strategy in the home. As a result, greater involvement of all the actors in this health process is suggested, bearing in mind that this will qualify the attendance to the population in the mental health area.